DOES THE MARKET REACT TO A NEW ISLAMIC INDEX AMID THE COVID-19 PANDEMIC IN INDONESIA? - Jaharuddin Jaharuddin; Masruri Muchtar; Ahmad Rodoni; Bambang Sutrisno (Jurnal Ekonomi Trisakti, 2022)
In collaboration with the Sharia Economic Community (MES), Indonesia Stock Exchange (IDX) launched a new Islamic index called IDX-MES BUMN 17 on 29 April 2021. This study aims to investigate market reaction to the issuance of the IDX-MES BUMN 17 index. This study employs event study methodology. The market-adjusted model measures the abnormal return. The results show that overall, the market reacts negatively around the launch of the IDX-MES BUMN 17 index. The negative and significant abnormal return was only found on the eighth day after the index launch. This study has important implications for investors and regulators.